Systematization of the cranial vena cava in buffalos (Bubalus bubalis bubalis Simpson, 1945) - Amorim Júnior, Adelmar Afonso de (2002)
Twenty-five animals, Buffaloes fetus, with 5 to 9 months of age (15 females and 10 males) was analyzed by dissection after injected with latex substance. The fetuses were collected in a slaughterhouse and fixed in aqueous formol solution 10%. In the Cranial Vena Cava the following origin tributaries were observed: External right and left jugular veins and their collateral tributaries; the internal right and left jugular veins; the mediastinals and pericardials veins; the internal right and left thoracic; thymic vein; the right and left subclavian vein, the right and left costocervicalvertebral venous trunk, and occasionally the thoracic duct.